The Pompeii artifact life history project: Conceptual background and first season’s results - Theodore Peña, J. (Rei Cretariae Romanae Fautorum Acta, 2015)
This article presents a brief description of the conceptual background and first season’s results of the Pompeii Artifact Life History Project (PALHIP), a research initiative launched at Pompeii during the summer of 2012 under the direction of the author.